Kalkulator gerak lurus berubah beraturan dan gerak lurus berubah beraturan berbasis matlab - Santy Handayani; Didik Nur Huda (Navigation Physics : Journal of Physics Education, 2021)
Kinematics such as Regular Straight Motion and Regularly Changing Motion were early concepts studied in physics. To help calculate and understand this concept, an application for calculating regularly changing straight motion using matlab is made. Matlab GUI programming is used to simplify the calculation of kinematics cases. This GUI functions as a calculator so that it can help calculate kinematics cases.